2016
DOI: 10.1186/s12902-016-0108-8
|View full text |Cite
|
Sign up to set email alerts
|

Glucose levels as a prognostic marker in patients with ST-segment elevation myocardial infarction: a case–control study

Abstract: BackgroundPatients with myocardial infarction (MI) have a high mortality. Therefore, new risk markers and predictors of an adverse outcome for MI are required. The role of hyperglycemia in the development of cardiovascular complications in MI patients is still unclear.MethodsA total of 529 consecutive patients with the diagnosis of ST-segment elevation acute coronary syndrome within 24 h of the onset of symptoms were included in the study. All of the patients underwent blood glucose measurement at admission to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 14 publications
0
12
2
Order By: Relevance
“…In our study, out of 79 patients, recurrent MI was seen in 4 patients during the follow up period. This was lower in comparison to the studies of Karetnikova et al 1 In their study, 8 patients with diabetes mellitus and 10 patients without diabetes mellitus had shown recurrent MI during their one year follow up period.…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…In our study, out of 79 patients, recurrent MI was seen in 4 patients during the follow up period. This was lower in comparison to the studies of Karetnikova et al 1 In their study, 8 patients with diabetes mellitus and 10 patients without diabetes mellitus had shown recurrent MI during their one year follow up period.…”
Section: Discussioncontrasting
confidence: 69%
“…Our findings are consistent with the findings of Capes et al 8 They found that patients without diabetes who had glucose concentrations more than or equal to range 6.1-8.0 mmol/L had a 3.9-fold (95% CI 2.9-5.4) higher risk of death than patients without diabetes who had lower glucose concentrations. Similarly, in the present study, the mortality rate in diabetic patients was higher (40%) compared to non-diabetics (19%) which is comparatively higher than the findings of Karetnikova et al 1 In his study, the mortality rate was 14.82% in diabetic patients and 10% in non-diabetics (p>0.05).…”
Section: Discussioncontrasting
confidence: 49%
“…Moreover, a single site study in Russian by Karetnikova et al . [18] showed that hypoglycemia in diabetic patients with AMI was related with poor long-term outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, these investigators noted that hypoglycemia was associated with an increased mortality rate and that an increase in the average glucose level during the ICU stay was associated with increased mortality. Karetnikova et al studied 529 patients admitted with an ST-segment elevation myocardial infarction [16]. They found a linear association between the blood glucose level and inhospital mortality in nondiabetic patients.…”
Section: Studies In Specific Patient Groupsmentioning
confidence: 99%